Charismatic Christianity
VIII, 236 p.
Keywords: The charismatic movement has a high profile in contemporary Christianity. The book's contributors include insiders and outsiders, charismatics and sociologists; with Britain as their focus, they trace the movement's international connections, historical development and variety. The book provides a wealth of information and analysis which will interest both those within the movement and students of religion wanting to know more about it.